ANALYZING PERCEIVED WRITING DIFFICULTIES THROUGH THE SOCIAL COGNITIVE THEORY - Rahmat, Noor; Arepin, Mazlen; Yunos, D; Rahman, Sharifah (PEOPLE: International Journal of Social Sciences, 2017)
Writing can both be considered as social and cognitive activity. Nevertheless, among the four language skills, writing skill is among the least liked by many ESL students. Students find writing a tedious process. Teachers find writing a difficult skill to teach. Writing skill involves planning, writing, editing, and perhaps re-writing and these skills are not easily taught nor learnt. Psychologists believe that expectations play a very important role in students’ success in learning. Writing teachers would agree that among some of the reasons why students cannot write well is because they find ESL academic writing difficult. This research looks into students’ perceived difficulties towards ESL academic writing. 373 students from seven faculties participated in this study. The participants responded to 25 items on 5 Likert-scale (always, very often, sometimes, rarely and never). The questionnaires were analyzed to determine the students’ perceived difficulties on ESL academic writing. Mean score, t-test and one way ANOVA were used to report on the findings. Findings revealed students found writing to be difficult for several reasons.